2017
DOI: 10.1097/inf.0000000000001653
|View full text |Cite
|
Sign up to set email alerts
|

Neuroborreliosis in Swedish Children: A Population-based Study on Incidence and Clinical Characteristics

Abstract: This study is the largest so far in a pediatric population. The incidence of neuroborreliosis was higher than in previous European reports. This might be explained by increased Borrelia awareness, the distribution of tick population in Sweden, and the possibility that Swedish children more frequently play outdoors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
5
17
0
3
Order By: Relevance
“…We found that the incidence was highest in children younger than 10 years; this is in agreement with a recent study on Lyme neuroborreliosis in children younger than 15 years in the south-western part of Sweden, where the incidence rate was lower in 10–14 year-olds compared with those younger than 10 years [15]. A similar age distribution with a higher incidence of Lyme neuroborreliosis in 5–10 year-old children and people older than 55 years was seen during an evaluation of the national surveillance system in Denmark [6].…”
Section: Discussionsupporting
confidence: 93%
“…We found that the incidence was highest in children younger than 10 years; this is in agreement with a recent study on Lyme neuroborreliosis in children younger than 15 years in the south-western part of Sweden, where the incidence rate was lower in 10–14 year-olds compared with those younger than 10 years [15]. A similar age distribution with a higher incidence of Lyme neuroborreliosis in 5–10 year-old children and people older than 55 years was seen during an evaluation of the national surveillance system in Denmark [6].…”
Section: Discussionsupporting
confidence: 93%
“…Lyme neuroborreliosis (LNB), which is caused by a complex of Gram-negative spirochaetes called Borrelia burgdorferi sensu lato and transmitted to humans by the Ixodes ricinus tick, is the most serious manifestation of Lyme disease (LD) [1]. Borrelia constitutes a common cause of bacterial infection of the central nervous system (CNS) among children and adults in Sweden [2][3][4][5] and Finland [6]. According to the diagnostic criteria for LNB [7], mononuclear pleocytosis must be present in the cerebrospinal fluid (CSF), and this is an indicator of an active infection.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils and their activation products are important early during infection, and they most likely affect the course and outcome of many diseases. With LNB, children tend to seek medical care earlier than adults owing to their having higher frequencies of meningeal symptoms and facial nerve palsy [3,4,21]. Therefore, we systematically evaluated whether NETs could be detected (using two different assays) in the CSF samples of children and adults with LNB, as well as in CSF samples from other infections and disorders affecting the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Lyme neuroborreliosis (LNB) is the second most frequent LB manifestation and most commonly caused by B. garinii [ 1 3 ]. The incidence of LNB in Sweden is 2.8/10.000 children [ 8 ]. The Borrelia spirochetes in the skin may spread into the central nervous system in two alternative ways: either through the bloodstream or along peripheral nerves [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facial nerve palsy is the most commonly occurring clinical manifestation of LNB in children and it is often present at the ipsilateral side of the tick bite or EM [ 10 ]. Headache, fever and/or fatigue are common unspecific symptoms in LNB [ 8 , 11 ] and occasionally, LNB presents with normal neurological examination [ 12 ]. Thus, the LNB diagnosis requires both clinical signs and symptoms attributable for LNB and laboratory testing, according to European guidelines [ 2 , 13 ].…”
Section: Introductionmentioning
confidence: 99%